Occupational safety and health in occupational performance in the Provincial Municipality of Chiclayo, 2016 - Díaz Alama, Milagros Liseth (2017)
This article proposes a training development plan in occupational safety and health to improve the labor performance of workers in the Provincial Municipality of Chiclayo. The study was made to a population of 30 workers in the area of remuneration. The study was done using a Pre-Experimental design, applying a pretest and a post-test, the type of research is explanatory and applied, the techniques used were textual records, bibliographic records. It was used as field technique the survey that has contained 32 questions on occupational safety and health in the work performance data that have been collected within the established time, for its validity and reliability the instrument achieved a reliability of 0,926 in Cronbach's alpha. The objective was to determine the influence of the training development plan on occupational safety and health in the labor performance of workers in the Provincial Municipality of Chiclayo. As a result it was evident that extrinsic and intrinsic factors directly influence work performance. A good working environment, safe and reliable, elevates the work performance.